Population Structure, Genetic Diversity and Differentiation of Triplophysa tenuis in Xinjiang Tarim River - Huo, Bin; Liu, Xuan; Chen, Shengao; Liu, Jieya; Zhou, Qiong; Shen, Jianzhong; Li, Dapeng; Tang, Rong; Chen, Jing; Zhou, Xiaoyun (Frontiers in Genetics, 2022)
Triplophysa tenuis is an important indigenous fish in the Xinjiang Tarim River. In this study, we collected 120 T. tenuis individuals from eight T. tenuis populations in the Tarim River. Through genotyping-by-sequencing (GBS), a total of 582,678,756 clean reads were generated for all the genotypes, and after quality filtering, 595,379 SNPs were obtained for the population genetic analyses. Multiple genetic parameters showed that the eight T. tenuis populations had high genetic diversity. Phylogenetic tree analysis indicated that all T. tenuis individuals were divided into five branches, the individuals from the north of Tarim River were grouped into cluster 1 (SF and WS) and cluster 3 (DWQ, TKX, and KZE), while the AETS, WLWT and LF individuals from the south of Tarim River were clustered into cluster 2. The result was consistent with the admixture analysis, which supported that the eight T. tenuis populations were clustered into three subgroups. Furthermore, the pairwise FST values and genetic distance indicated that there was a large genetic differentiation between WS and other T. tenuis populations. Collectively, this study provides valuable genome-wide data for the conservation of natural T. tenuis populations in the Tarim River.